2017
DOI: 10.29252/irjns.3.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Topography of Sylvian Fissure and Central Sulcus as Neurosurgical Landmarks: an Anatomical Study Using Cadaveric Specimens in Iran

Abstract: Background and Aim: In the present study, the cerebral surface landmarks in human fresh autopsy specimens were investigated. Methods and Materials/Patients: Totally, 37 fresh adult autopsy human brain specimens from the Rasht Forensic Medicine Center were enrolled. Four specimens were excluded because of some traumatic injuries to cerebral cortex. Demographic information of all cases was obtained. Length of bilateral central sulcuses and posterior ramous of Sylvian fissures, thickness of superior, middle, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Since Mashouf et al did not find any significant differences in the measured values of left and right brain hemisphere and concluded that the cerebral surface landmarks are similar on the left and right sides 7 ; therefore, we did not measure SF length in our study.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Since Mashouf et al did not find any significant differences in the measured values of left and right brain hemisphere and concluded that the cerebral surface landmarks are similar on the left and right sides 7 ; therefore, we did not measure SF length in our study.…”
Section: Discussionmentioning
confidence: 83%
“…2 SF is the most recognizable part of the outer layer of the brain making it one of the main anatomical indices during neurosurgery. 7 The types of SF varied with patients age which might be due to difference in brain volume with respect to age. 6 According to the study conducted by Maslehaty et al, wide SF types 1 and 3 occur more frequently in patients older than 60 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation